Integrating AI-generated client simulations in architectural education - Gunagama, M. Galieh; Fildzah Zatalini Zakirah (Universitas Islam Indonesia, 2025)
This study examines the integration of AI-generated client simulations to address a critical gap in architectural education: the limited exposure to unpredictable, human-centric client dynamics in traditional studio pedagogy. Conducted within the Integrated Design Studio (IDS) at Universitas Islam Indonesia, the research employed ChatGPT to generate randomized client profiles across seven categories for 10 students. Qualitative and quantitative analyses revealed that AI simulations significantly enhanced students’ adaptability, creativity, and critical thinking, compelling them to resolve